2021
DOI: 10.3390/ijms222212305
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and the Cardiac Parasympathetic Nervous System in Hypertension

Abstract: The renin–angiotensin–aldosterone system (RAAS) impacts cardiovascular homeostasis via direct actions on peripheral blood vessels and via modulation of the autonomic nervous system. To date, research has primarily focused on the actions of the RAAS on the sympathetic nervous system. Here, we review the critical role of the RAAS on parasympathetic nerve function during normal physiology and its role in cardiovascular disease, focusing on hypertension. Angiotensin (Ang) II receptors are present throughout the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 141 publications
(223 reference statements)
0
18
0
1
Order By: Relevance
“…The additional entrance of plasma angiotensin II, via absorptive transcytosis, augmented its availability within the PVN, NTS, and RVLM and potentiated the autonomic dysfunction, as recorded in SHR-S rats. Indeed, Pyner (2021) and Shanks and Ramchandra (2021) reviewing previous studies clearly demonstrated that within the autonomic areas the augmented angiotensin II content activates premotor sympathetic and impairs parasympathetic neurons. It is important to note that increased hypertension-induced absorptive transcytosis was reduced and completely normalized after exercise training (Buttler et al, 2017;Fragas et al, 2021), as was the brain reninangiotensin system hyperactivity (Masson et al, 2014;Chaar et al, 2015;Raquel et al, 2022).…”
Section: Discussionmentioning
confidence: 76%
“…The additional entrance of plasma angiotensin II, via absorptive transcytosis, augmented its availability within the PVN, NTS, and RVLM and potentiated the autonomic dysfunction, as recorded in SHR-S rats. Indeed, Pyner (2021) and Shanks and Ramchandra (2021) reviewing previous studies clearly demonstrated that within the autonomic areas the augmented angiotensin II content activates premotor sympathetic and impairs parasympathetic neurons. It is important to note that increased hypertension-induced absorptive transcytosis was reduced and completely normalized after exercise training (Buttler et al, 2017;Fragas et al, 2021), as was the brain reninangiotensin system hyperactivity (Masson et al, 2014;Chaar et al, 2015;Raquel et al, 2022).…”
Section: Discussionmentioning
confidence: 76%
“…Zanella (Zanella, 2018) analyzed that the quality of life after the intervention with meditation may be associated with an increase in the parasympathetic predominance, which acts on emotional flexibility and resistance to stress, acting in the improvement of the psychological domain. Shanks (Shanks et al, 2021) points out that the parasympathetic mechanism is broad and regulates heart rate, blood pressure, and breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II is the main effector of the renin-angiotensin-aldosterone system (RAAS), and studies have shown that Ang II promoted the development of hypertension through RAAS system ( 118 ). In hypertensive mice induced by Ang II, TMAO changed the structure of Ang II by enhancing folding and processing of proteins, thereby prolonging the duration of hypertensive effect ( 119 ).…”
Section: Tmao and Hypertensionmentioning
confidence: 99%